Optimizing the reaction parameters for synthesizing Carboxymethyl Cellulose from Hyphaene thebaica (Doum palm) leaves (Indian Journal of Chemistry (IJC), 2024)
The current investigation focused on optimizing reaction conditions for preparing carboxymethyl cellulose (CMC) using a new source Hyphaene thebaica leaves. The CMC produced under optimal conditions was subsequently characterized by 1H-NMR, FTIR, and TGA techniques. Various solvent mixtures, including a combination of ethanol and isopropanol, were employed in the study. Additionally, different temperatures, reaction durations, and quantities of monochloro acetic acid (MCAA) were utilize. The highest degree of substitution (DS) was found to be 1.16. This result was achieved by reacting MCAA with cellulose at a molecular ratio of 1:4.5 for 3 hours at 65 °C using a solvent combination of (1:1). The produced CMC has an exceptionally unique physical characteristics creamy color and solubility (92%). The presence of a carbonyl group absorption signal in FTIR at 1734 cm-1 indicated the production of CMC. In addition, the application of Thermogravimetric analysis (TGA) demonstrated that carboxymethyl cellulose exhibits lower thermal stability in comparison to its native cellulose.